2018
DOI: 10.1038/s41598-017-18886-7
|View full text |Cite
|
Sign up to set email alerts
|

Competition among the attentional networks due to resource reduction in Tibetan indigenous residents: evidence from event-related potentials

Abstract: This study used the attention network test (ANT) to evaluate the alerting, orienting, and executive network efficiencies of attention related to indigenous residents who were born and raised until early adulthood in different high-altitude areas (2900-m, 3700-m, and 4200-m) at the same location (3700-m) where these residents had been living for approximately 2 years in Tibet. We further applied the event-related potential (ERP) method to identify the underlying neurophysiological basis. Based on the ANT, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…RRN is a subcluster of the P3 component, which is an indicator of the brain's cognitive resources (Ma et al, 2016 ). It is directly related to the brain's executive control ability under hypoxia (Ma et al, 2015a , b ; Zhang et al, 2018 ). However, the underlying neural activity of this executive control system is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…RRN is a subcluster of the P3 component, which is an indicator of the brain's cognitive resources (Ma et al, 2016 ). It is directly related to the brain's executive control ability under hypoxia (Ma et al, 2015a , b ; Zhang et al, 2018 ). However, the underlying neural activity of this executive control system is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, individuals inhabiting extremely high altitudes (over 4,000 m), showed lower levels of performance in all executive tests (Virués-Ortega et al, 2011). However, in contrast, three different electrophysiological studies (Ma et al, 2015a; Richardson et al, 2011; Singh et al, 2004), reported that the influence of high altitude on cognition was present at altitudes above and below 4,000 m. Our previous study (Zhang et al, 2018), based on the attention network test (ANT), compared individuals residing at 2,900 m and 3,700 m with those residing at 4,200 m. The latter had lower orienting and executive function scores. They had larger N1 and P3 amplitudes than individuals in the other groups, which suggested that high-altitude could affect attentional function in individuals indigenous to different high-altitude areas and that a threshold may exist at 4,000 m (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 71%
“…Behavior and brain structure changes arising from hypoxia can be observed in a real high-altitude environment, and examined in simulated hypoxia situations. The hypoxia impact on the brain exhibits a significant altitude-dependent effect [5,6].…”
Section: Introductionmentioning
confidence: 99%